An Appraisal of the Internationalisation of Higher Education in Sub-Saharan Africa - Sintayehu Kassaye Alemu (Center for Educational Policy Studies Journal)
Over the past decades, the development of the internationalisation of higher education has revised the conceptual framework of higher education, enhanced its scope, scale and importance, and transformed its world, as well as reshaping relationships between countries. More powerful universities play a central role and are suppliers of knowledge, whereas weaker institutions and systems with fewer resources and lower academic standards occupy a peripheral position and are consumers. The centre-periphery dichotomy in the internationalisation of higher education undoubtedly presents considerable challenges to the higher education institutions of the peripheries. For developing regions like Africa, higher education is an important instrument for socioeconomic development, and one of the strategies to improve and qualify higher education is internationalisation. In spite of various attempts to enhance the benefits of internationalisation, African higher education has continued to be peripheral, with relationships remaining asymmetrical, unethical and unequal. Along with some positive benefits, internationalisation has brought complicated implications and new challenges, such as the brain drain, cultural values, the commodification of higher education, the persistence of inequality between global north-south universities, and so on. The purpose of the present paper is to highlight the challenges and unintended consequences of the internationalisation of higher education, with a particular focus on Africa.